FORMATION OF INNOVATIVE STRATEGIES OF THE ENTERPRISE : METHODS AND PROBLEMS - Kholikova Sabokhat Abdukarimovna (Scholar Express Journals, 2022)
The article reveals the concept of "innovative strategy", provides a classification of such a strategy. The ratio of corporate and innovative strategies of the company is analyzed. According to the author, the key task of developing and implementing an innovation strategy is to organize the flow of innovations and ideas. Approaches to the formation of the company's innovative strategy are proposed. First of all, it is necessary to develop tools for the formation of this flow, that is, methods for searching for and adapting innovations that provide a steady stream of innovations (innovations) to achieve the strategic goals of the company, as well as sources, systems for collecting and processing information, organizing work with knowledge carriers
Keywords: innovations; innovation strategy; intellectual capital; corporate strategy